Pengembangan Materi Ajar Teks Laporan Hasil Observasi Berbasis Audio Visual Project Based Learning - Disra, Disra; Karumpa, Aco; Razak, Nur Khadijah (Paedagogie, 2025)
This research uses Dick and Carey's development model which is adapted in five stages: preliminary study, design, development, evaluation and revision, and dissemination. Research instruments include validation sheets, teacher and student response questionnaires, and learning outcome tests. This research is based on the low interest and writing ability of students due to the lack of interesting learning resources and contextual learning approaches. The purpose of the research is to produce prototypes, feasibility, practicality and effectiveness of Indonesian language teaching materials to write a report text of audio visual-based observation results with a project based learning model for Class VIII.A State Junior High School 7 Alla Enrekang Regency. Trial subjects include material experts, media experts, Indonesian teachers, and class VIII.A students. The feasibility of the material is obtained from expert validation, practicality from teacher and student questionnaires, as well as the effectiveness of pretest and posttest results. Analysis using quantitative and descriptive statistical data. Effectiveness data is obtained from students' pretest and postest learning results, before and after using Teaching Materials for Writing Audio Visual Based Observation Results Report Text with project based learning Model. The data analysis techniques used are quantitative data analysis for the feasibility, practicality, and effectiveness of the Teaching Material of Writing Audio Visual Based Observation Results Report Text with the project based learning model. Then analyze descriptive statistical data and polygon analysis to analyze students' pretest and posttest learning results. The research results show that the teaching material of the observation report text consists of learning resources and learning activities. Validation of material experts obtained an average score of 4.8 (very decent), and media experts 4.3 (worthy). Student response reaches 100% (very practical), and the average student posttest score is in the range of 80–100 (effective). Based on the results of the data analysis, it was concluded that the development of teaching materials for writing audio visual-based observation reports with a project-based learning model is suitable, practical, and effective for students in class VIII.A of SMPN 7 Alla Enrekang Regency.